Exame citológico do colo uterino: adesão das mulheres na atenção básica do município de João Pessoa-PB - Oliveira, Ana Eloísa Cruz de (2016)
The cytological examination of the cervix is a simple, fast and easy method to perform, which has proven its effectiveness, efficiency and it is the most suitable for the screening of cervical cancer. This study aimed to assess adherence of women to the cytological examination of the cervix in Primary Health Care in the city of João Pessoa-PB through an exploratory and descriptive survey, with quantitative approach, developed in 20 Family Health Units in the same city, with a sample of 384 women who looked for attendance in these health services. On data collection, it was used an instrument previously developed for the realization of the structured interview technique, in which social and demographic issues were related to women and to specific issues that contemplated aspects that influence in relation to the realization of cytological examination, and subsequently they were analyzed by descriptive statistics, as well as factorial analysis and correspondence analysis. The predominant profile was that of women with age range 30-39 years old, of mixed race, in consensual union, Catholic , poorly educated, predominating the 2nd phase of incomplete primary education and low family income - from one to two salaries. It could see that most of the interviewees has performed cytological examination at least once and the majority performed it annually. Among the aspects that make it easy, have been identified, the information they get previously about the exam, educational work, the prevention of cervical cancer, the professional service, the reception at the health service, the presence of vaginal problems, routine of attendance at the health unit and the medical recommendation. Although talking about the aspects that make it difficult, were highlighted, shame, anxiety, deadline for getting the test results back, routine of attendance at the health unit, the position to take the examination, no vaginal problems, reception at the clinic, absence of a partner, pain, professional service, family issues, the examination by a male professional, lack of knowledge about the exam, fear to take the examination and also of cancer, body changes with age and multiparity by vagina. Among the results, it was observed that much of the sample used in this study had a defined frequency to take the examination, demonstrating a high degree of self-care. Those who did not have a definite schedule had higher barriers in relation to the cytological examination, influencing negatively on self-care practiced by those interviewed. Through the results of this study, it was observed that care in cervical cancer prevention should not be only directed to the technical aspects of cytological exam. In this context, it is necessary to focus on the behavior and feelings of women towards the procedure by developing educational activities and promoting forums for dialogue. With this, it is thought that it will be possible to facilitate the access of women to the test and stimulate self-care in relation to the prevention of cervical cancer.